MicroRNAs and tRNA-Derived Small Fragments: Key Messengers in Nuclear–Mitochondrial Communication - Meseguer, Salvador (Frontiers in Molecular Biosciences, 2021)
Mitochondria are not only important as energy suppliers in cells but also participate in other biological processes essential for cell growth and survival. They arose from α-proteobacterial predecessors through endosymbiosis and evolved transferring a large part of their genome to the host cell nucleus. Such symbiotic relationship has been reinforced over time through increasingly complex signalling mechanisms between the host cell and mitochondria. So far we do not have a complete view of such mechanisms, which allow the mitochondria to communicate their functional status to the nucleus and trigger adaptive and compensatory responses. Recent findings place two classes of small non-coding RNAs (sncRNAs), microRNAs (miRNAs) and tRNA-derived small fragments (tRFs or tsRNAs), in such scenario, acting as key pieces in the mitochondria-nucleus cross-talk. This review highlights the emerging roles and the interrelation of these sncRNAs in different signalling pathways between mitochondria and the host cell. Moreover, we describe in what way alterations of these complex regulatory mechanisms involving sncRNAs lead to diseases associated with mitochondrial dysfunction. In turn, these discoveries provide novel prognostic biomarker candidates and/or potential therapeutic targets.